2021
DOI: 10.3389/fpsyt.2021.712231
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the GABA Receptor Subunit Gene Polymorphism and Childhood Sexual Abuse on Processing Speed in Major Depression and Suicide Attempt

Abstract: Background: Suicide is moderately heritable and also more common in those who report childhood abuse. Previously, it was found that allele A of GABRG2 (GABA A receptor subunit gamma2) polymorphism rs211034 was protective in a suicide attempt (SA). Hence, it was proposed that rs211034 may interact with childhood trauma to influence cognitive deficits related to SA or depression risk. Genetic variants may predict the benefits of certain cognitive treatments.Methods: A total of 52 individuals who had attempted su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Our previous study found slower processing speed in depressed patients, regardless of suicide attempt history. Furthermore, depressed attempters showed enhanced positive-word response time compared to depressed non-attempters [ 27 ]. Therefore, based on these previous findings, the performance of SST was no longer used for statistical analysis, but for ML in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study found slower processing speed in depressed patients, regardless of suicide attempt history. Furthermore, depressed attempters showed enhanced positive-word response time compared to depressed non-attempters [ 27 ]. Therefore, based on these previous findings, the performance of SST was no longer used for statistical analysis, but for ML in this study.…”
Section: Methodsmentioning
confidence: 99%
“…23 CT frequencies were found to be similar to those reported in previous studies using the CTQ in SA patients. [41][42][43] This study did not used a healthy control group and to our knowledge, there are not Mexican studies that analyzed the CT in a healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, more recent studies indicate that the SST has poor concurrent validity and cannot effectively differentiate persons with versus without SA history (Niu et al, 2021;Wilson et al, 2019). Overall, attentional bias to suicide-related words is not robustly associated with SITB (Becker et al, 1999;Cha et al, 2017Cha et al, , 2018Chung & Jeglic, 2016Niu et al, 2021;Stewart et al, 2017;Tavakoli et al, 2021;Williams & Broadbent, 1986;Yin et al, 2021), and does not account for unique variance in SA history when controlling for depressive symptoms (Chung & Jeglic, 2016. Thus, SST is not a robust predictor of suicide risk.…”
Section: Stroop Testmentioning
confidence: 99%